Influence of poly(methyl acrylate) additive on cold flow properties of coconut biodiesel blends and exhaust gas emissions. (February 2017) - Monirul, I.M.; Kalam, M.A.; Masjuki, H.H.; Zulkifli, N.W.M.; Shahir, S.A.; Mosarof, M.H.; Ruhul, A.M.
Abstract: Biodiesel comprises fatty acid esters and is used as an alternative fuel for diesel engines. However, biodiesel has poor cold flow properties (i.e., CP, CFPP and PP) than mineral diesel fuel. This study aims to reduce the PP, CFPP and CP of coconut biodiesel (CB) blends using poly(methyl acrylate) (PMA) additives and investigate their effects on single-cylinder four-stroke diesel engine performance and exhaust gas emission. DSC and TGA were used to observe crystal behavior and thermal stability of the biodiesel fuel blends. Engine performance and emission were analyzed by Dynomax-2000 software and gas analyzer, respectively. Results showed that 20% of CB blended with diesel and 0.03 wt% of PMA showed significant improvement in the PP, CFPP and CP. Other properties of B20 with additives met the requirements of ASTM D6751. The BSFC of B20 with PMA was reduced by 3.247%, whereas the BTE was increased by 2.16%, compared with those of B20. Burning B20 with PMA increased the NO emission by 2.15%, whereas HC, CO and smoke emissions were 19.81%, 13.35% and 3.93% lower than those of B20, respectively. Therefore, CB20 blend with 0.03 wt% PMA can be used as an alternative fuel in cold regions without compromising fuel quality. Highlights: Properties of B20 biodiesel blends with 0.03 wt% PMA satisfied with ASTMD6751 . The CFP of biodiesel blend with 0.03 wt% of PMA significantly decreased. PMA modified the wax crystal rate and crystallization behavior. The addition of PMA reduced the BSFC of biodiesel blends. The addition of PMA reduced HC, CO and smoke and slightly increased NO emission.